2013
DOI: 10.1021/cn400094w
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Properties and Mechanisms of Resveratrol inin Vitroandin VivoExperimental Cerebral Stroke Models

Abstract: Resveratrol, a natural stilbene present at relatively high concentrations in grape skin and seeds and red wine, is known for its purported antioxidant activity in the vascular and nervous systems. In contrast to its direct antioxidant role within the central nervous system, recent research supports a protective mechanism through increasing endogenous cellular antioxidant defenses, which triggers a cascade of parallel neuroprotective pathways. A growing body of in vitro and in vivo evidence indicates that resve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 140 publications
(267 reference statements)
2
98
0
2
Order By: Relevance
“…In the observed test group of rodents with models of stroke, a reduced stroke impact area and improved cognitive functions after parenteral and oral intake of RSV were observed. Best neuroprotective effects of RSV occur when the intake took place during or immediately after stroke [40]. RSV has also a positive effect in Alzheimer's disease because of its ability to reduce cognitive disorders, interneural amyloid beta deposit, hyperphosphorylation of tau protein in the hippocampus and its neuroprotective properties.…”
Section: The Biological Activity Of Resveratrolmentioning
confidence: 99%
“…In the observed test group of rodents with models of stroke, a reduced stroke impact area and improved cognitive functions after parenteral and oral intake of RSV were observed. Best neuroprotective effects of RSV occur when the intake took place during or immediately after stroke [40]. RSV has also a positive effect in Alzheimer's disease because of its ability to reduce cognitive disorders, interneural amyloid beta deposit, hyperphosphorylation of tau protein in the hippocampus and its neuroprotective properties.…”
Section: The Biological Activity Of Resveratrolmentioning
confidence: 99%
“…In order to eliminate excess free radicals, antioxidants must be used to preserve the balance between oxidation and reduction in vivo, thereby preventing the development of diseases. Studies have found that natural antioxidants such as hawthorn flavonoids, green tea polyphenols, resveratrol and the traditional Chinese medicine prescription Buyang Huanwu Decoction (BYHWD) are effective in the prevention and treatment of cardiovascular and cerebral diseases [13][14][15][16][17][18][19] .…”
Section: Use Of Natural Antioxidants In the Prevention And Treatment mentioning
confidence: 99%
“…OS-induced neurocyte apoptosis is a primary contributor to neurological disease with OS in the reoxygenation/reperfusion setting of stroke constituting a major driving force for neurocyte apoptosis (8)(9)(10). The immediate supplement of exogenous antioxidants has been demonstrated to decrease neuronal mortality and ease the burden of stroke in vivo and in vitro (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The immediate supplement of exogenous antioxidants has been demonstrated to decrease neuronal mortality and ease the burden of stroke in vivo and in vitro (8)(9)(10). By contrast, OS derived from microglial activation in PD induces neurocyte apoptosis and consequently assists the degeneration of dopaminergic neurons that is a marked pathological feature of PD (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation